A case series of inactivated Japanese encephalitis virus vaccination associated with positive West Nile virus blood donor screening nucleic acid tests. Issue 5 (10th March 2020) - Drews, Steven J.; Makowski, Kai; Wood, Heidi; Dimitrova, Kristina; Yan, Matthew T.S.; Young, Dale; Skeate, Robert; Ng, Michiko; Hawes, Gordon; Fearon, Margaret; Bigham, Mark
ABSTRACT: BACKGROUND: West Nile Virus (WNV) is a member of the Japanese Encephalitis (JE) serocomplex within the Flaviviridae family. We report four whole blood donors and one plasma donor with WNV nucleic acid test (NAT)‐reactive donations between September 2018 and November 2019, following recent Japanese Encephalitis virus (JEV) vaccination. CASE SERIES: Cases 1 and 4 had reactive WNV NAT donations 1 day after receiving the JEV vaccine. Case 2 had a reactive WNV donation 3 days after receiving the JEV vaccine. Case 3 had a reactive WNV NAT donation 3 days after returning from Arizona and 1 day after receiving the JEV vaccine. Case 5 had a reactive WNV donation the same day as receiving the JEV vaccine. STUDY DESIGN AND METHODS: WNV screening used the Roche cobas WNV nucleic acid test (NAT) (Roche Molecular Systems). Reference testing on WNV‐reactive donations was carried out by the National Microbiology Laboratory (NML). JEV vaccine dilutions were also analyzed. RESULTS: Supplemental NAT was negative for WNV and JEV for Cases 1, 3, and 5. Case 2 had a weak amplification curve for one of two JEV NAT targets. Case 4 was JEV NAT‐positive, WNV NAT‐negative. Serologic testing on donation specimens for Cases 2, 4, and 5 did not support recent or remote WNV infection. JEV vaccine dilutions were detected by both cobas and supplemental NAT. CONCLUSIONS: We recommend implementing a temporary blood donor deferral following a JEV vaccination, if screening utilizes a WNV assay with the capability of detecting other members of the JE serocomplex.